Effect of calcium sulphoaluminate cement on mechanical strength and waterproof properties of beta-hemihydrate phosphogypsum. (10th May 2020) - Jin, Zihao; Ma, Baoguo; Su, Ying; Lu, Wenda; Qi, Huahui; Hu, Penghui
Highlights: The compressive strength and softening coefficient of β-HPG can be improved to 21.5 MPa and 0.66 with the content of 20% SAC. SAC can increase the drying shrinkage and decrease the pore size of β-HPG. Ettringite and aluminate hydroxide are formed to optimize the microstructure and improve the properties of β-HPG. Abstract: Beta-hemihydrate phosphogypsum (β-HPG) as a cementitious material obtained from the dehydration of phosphogypsum (PG) can be widely used for the preparation of building materials. The main problems for its utilization are its low mechanical strength and poor waterproof properties. In this study, calcium sulphoaluminate cement (SAC) was used to improve the properties of β-HPG. The compressive strength, flexural strength, ratio of compressive to flexural strength, water absorption rate and softening coefficient were measured. The volume stability, pore structure and microstructure were characterized to evaluate the effect of SAC. The results show that SAC can improve the mechanical strength and waterproof properties of β-HPG significantly. With the addition of 20% SAC, the increase of drying shrinkage is relatively small, and the compressive strength and softening coefficient were 21.5 MPa and 0.66, increasing by 60.85% and 96.04% respectively compared to the mixture without SAC. Specifically, ettringite and aluminate hydroxide are formed and interconnected with calcium sulfate dihydrate to improve the waterproof properties of β-HPG under the effect of SAC. The crystal morphology of calcium sulfate dihydrate changes from long rods to short columns, and the pore size and total porosity of the mixture decrease, resulting in the improvement of the mechanical strength of β-HPG. The purpose of this work is to optimize the properties of β-HPG and provide a high performance cementitious material for the effective utilization of PG.